A construção da leitura e da escrita infantil e a pratica do estágio supervisionado - Santos, Camila Fleck dos (2015)
This Master's thesis is included in the search line Training, Knowledge and Development Graduate Program Professional, Master of Education, Federal University of Santa Maria (UFSM). We have as a general objective of this research to understand the conceptions of academics of the Faculty of Education of UFSM, night and day on reading and children's writing and how these permeate the practices in supervised training. The starting point of the theoretical assumptions that include studies of Nóvoa (2009), Imbernon (2009, 2011) and Vaillant and Marcelo Garcia (1999, 2012), pepper and Lima (2011), Pepper (2010), Smith (1987, 2011a a, b, c, 2012, 2013), and Smith Teberosky (1999), Teberosky (1987), Mitchell (2004, 2005), Mortatti (2004, 2006) among others. The research was carried out from a qualitative approach, socio-cultural nature based on the studies of Minayo (1992, 2009), Freitas (2002), Bolzan (2002), Connelly and Clandinin (1995), Vygotsky (2007). To collect data, we conduct narrative interviews with six academic enrolled in Supervised Internship disciplines of the Pedagogy course, day and night, UFSM, as well as analysis of reports, articles and planning for the stage. The analysis was conducted from recurrences narratives indicated that the two categories of analysis: teacher learning and training processes. Thus, it was possible to recognize the trajectories of students in initial training, identifying the conceptions of learning to be a teacher and the relationship between the experienced situations and theoretical constructs about reading and writing. Thus, we understand that initial training needs to be organized in order to promote training experiences focused on areas of professional activity; no need to make mechanisms that foster awareness of the autoformativa dimension; the teaching learning is characterized by contradictions that allow students to advance in the construction of knowledge; extracurricular formative experiences stood out because they were designed as an opportunity to meet the possible professional performance context and to promote the relationship between theory and practice; the practice on their empties, it is necessary for reflection on practice and practice is incorporated into the teaching routine; and finally, it noted that the conceptions about the construction of reading and children's writing, academic study participants are being prepared. Therefore, we understand that learning to be a teacher in initial training has its basis in the formative processes will constitute the structure of the relations that the academic setting will during its journey and experiences in different spaces. Thus, the views of academics on the reading and writing will be built from a set of life experiences along the formative path.